Regulatory practice in the European telecommunications sector: Normative justification and practical application - Margit A. Vanberg; Gordon J. Klein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The telecommunications sector is characterized by economies of scale and scope, high sunk costs, and strong network effects. This combination may facilitate monopolization and abuse of market power. The present study evaluates the need for sector-specific regulation in this sector. It is shown that there is a conflict between static and dynamic efficiency goals. A comparison of two prominent regulatory approaches for the telecommunications sector shows that the disaggregated approach takes account of this conflict most adequately, as it is committed to minimal regulation. The European regulatory framework for electronic communications markets is based on economic theory, and could principally be used to limit regulation to network areas in which stable networkspecific market power is localized. However, especially the criteria for the assessment of significant market power (SMP) are applied too liberally, such that, in practice, overregulation has resulted.
urn:nbn:de:bsz:180-madoc-19430
Keywords: 380; Telekommunikationspolitik; Regulierung; Wirtschaftliche Effizienz; Wettbewerbspolitik; Marktmacht; EU-Staaten